Family Members' Perceptions of Their Psychological Responses One Year Following Pediatric Intensive Care Unit (PICU) Hospitalization: Qualitative Findings From the Caring Intensively Study - Rennick, Janet E.; Knox, Alyssa M.; Treherne, Stephanie C.; Dryden-Palmer, Karen; Stremler, Robyn; Chambers, Christine T.; McRae, Lyndsey; Ho, Michelle; Stack, Dale M.; Dougherty, Geoffrey; Fudge, Hailey; Campbell-Yeo, Marsha (Frontiers in Pediatrics, 2021)
Introduction: PICU hospitalization can have a profound impact on child survivors and their families. There is limited research on children’s long-term recovery within the context of the family following critical illness. This study aimed to explore children’s and parents’ perceptions of long-term psychological and behavioral responses within the context of the family one year following PICU hospitalization. Materials and Methods: Caring Intensively is a mixed methods multi-site prospective cohort study that aims to examine children’s psychological and behavioral responses over a 3-year period following PICU hospitalization. In this study, part of the qualitative arm of Caring Intensively, an interpretive descriptive design was used to explore children’s recovery one-year post-discharge. Purposive sampling was used to select 17 families, including 16 mothers, 6 fathers, and 9 children. Semi-structured, audio-recorded interviews were conducted. Data were analyzed iteratively using the constant comparison method. Results: Families described efforts to readapt to routine life and find a new normal following PICU hospitalization. Finding a New Normal consisted of four major themes: 1) Processing PICU Reminders and Memories, 2) Changing Perceptions of Health and Illness, 3) We Are Not the Same, and 4) Altered Relationships. Participants described significant emotional and behavioural changes during the year following discharge. The psychological impact of individual family members’ experiences led to changes in their sense of self, which affected family dynamics. PICU memories and reminders impacted participants’ perceptions of childhood health and illness and resulted in increased vigilance. Parents and siblings demonstrated increased concern for the child survivor’s health, and the experience of long absences and new or altered caregiving roles resulted in changes in relationships and family dynamics Conclusion: PICU hospitalization impacted the psychological well-being of all family members as they sought to re-establish a sense of normalcy one year following discharge. Parent and child experiences and responses were closely interconnected. Findings highlight the importance of increased follow-up care aimed at supporting the family’s psychological recovery.